STRATEGI BRANDING KOPI SEKANAK “KOPI PARA RAJA“ - Rofii, Eva Amalia; Mikasari, Dewi Aurora; Syafruddin Rais (Puslitabmas Batam Tourism Polytecnic, 2022)
This study reconnoiters how the richness and local wisdom of Malay culture are preserved through the taste of coffee which has its authentic philosophy so that it becomes a strong branding. Count on the marketing public relations strategy of pull, push and pass to build a brand awareness of